2014
DOI: 10.1111/cup.12279
|View full text |Cite
|
Sign up to set email alerts
|

SOX‐10 expression in cutaneous myoepitheliomas and mixed tumors

Abstract: SOX-10 is a relatively reliable marker for staining cutaneous myoepitheliomas. Cutaneous myoepitheliomas are notoriously difficult to diagnose, and the addition of SOX-10 to the repertoire of stains that can label this tumor is of practical utility. These results further support that cutaneous myoepitheliomas and cutaneous mixed tumors exist on a morphologic and immunophenotypic spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Sox-10 has recently been reported to be positive in some cases of cutaneous myoepithelioma (3 of 5 cases, 60%), however, it appears that these cases were of the classic variety rather than the syncytial variant of cutaneous myoepithelioma (16). Although no definitive conclusions could be drawn, in one of our cases where SOX-10 was performed, constituent cells were negative.…”
Section: Discussionmentioning
confidence: 94%
“…Sox-10 has recently been reported to be positive in some cases of cutaneous myoepithelioma (3 of 5 cases, 60%), however, it appears that these cases were of the classic variety rather than the syncytial variant of cutaneous myoepithelioma (16). Although no definitive conclusions could be drawn, in one of our cases where SOX-10 was performed, constituent cells were negative.…”
Section: Discussionmentioning
confidence: 94%
“…Ohtomo et al [10] also demonstrated that, in the context of basaloid salivary gland neoplasms, the IHC profile of SOX10 differs from that of DOG1 only in that it is diffusely expressed in normal myoepithelial cells which are negative for DOG1. In addition to salivary gland myoepithelial lesions, SOX10 is also a reliable marker for cutaneous myoepitheliomas (60%) and cutaneous mixed tumors (100%) [21]. …”
Section: Discussionmentioning
confidence: 99%
“…SOX10, a Schwannian and melanocytic marker also expressed in salivary gland myoepitheliomas, has also been shown to be useful as part of an immunohistochemical panel in distinguishing cutaneous myoepitheliomas. 27 CD34 and brachyury are consistently negative. 28 INI1 expression is lost in approximately 10% of adult soft-tissue myoepithelial carcinomas, [29][30][31] (Fig.…”
Section: Histopathologic and Immunohistochemical Findingsmentioning
confidence: 90%